Antimicrobial use for asymptomatic bacteriuria—First, do no harm. (13th January 2021) - Shpunt, Yana; Estrin, Inna; Levi, Yossef; Saadon, Hodaya; Ben-Yossef, Galit; Goldshtein, Lili; Klafter, Dan; Zilberman-Itskovich, Shani; Ben-David, Debby; Katz, David E.; Lazarovitch, Tsillia; Zaidenstein, Ronit; et al.
Abstract: Objective: Administration of antimicrobials to patients with asymptomatic bacteriuria (ASB) is a common error that can lead to worse outcomes. However, controlled analyses quantifying the commonality and impact of this practice are lacking. We analyzed the independent predictors for antimicrobials misuse in ASB and quantified the impact of this practice on clinical outcomes. Design: Retrospective case-control and cohort analyses for calendar year 2017. Setting: Tertiary-care, university-affiliated medical center. Patients: The study included adult (>18 years) patients with positive urine culture. Pregnant women, renal transplant recipients, and patients who underwent urologic procedures were excluded. Methods: ASB was determined according to US Centers for Disease Control and Prevention (CDC) criteria. Multivariable logistic regression models were constructed to analyze predictors and outcomes associated with antimicrobial use for patients with ASB. Results: The study included 1, 530 patient-unique positive urine cultures. Among these patients, 610 patients (40%) were determined to have ASB. Of the 696 isolates, 219 (36%) were multidrug-resistant organisms (MDROs). Also, 178 (29%) patients received antimicrobials specifically due to the ASB. Independent predictors for improper administration of antimicrobials were dependent functional status (adjusted odds ratio [aOR], 2.3; 95% CI, 1.4–3.6) and male sex (aOR, 2; 95% CI, 1.25–2.6). Use of antimicrobials was independently associated with re-hospitalizations (aOR, 1.7; 95% CI, 1.1–2.6) and later, acute Clostridioides difficile infections (CDI) in the following 90 days (aOR, 4.5; 95% CI, 2–10.6). Conclusions: ASB is a common condition, frequently resulting from an MDRO. Male sex and poor functional status were independent predictors for mistreatment, and this practice was independently associated with rehospitalizations and CDI in the following 90 days.